Main intercurrences with injectables in aesthetics and the impact on the patient's life: an integrative review (Research, Society and Development, 2023)
Introduction: The growing demand for aesthetic procedures in recent decades to contain aging marks, hyaluronic acid and botulinum toxin stand out in the areas of aesthetics and health. Facial treatment accounts for most of the procedures. Objective: To review in the literature the intercurrences that may occur during injectable facial aesthetic procedures. Methodology: The research is characterized as a bibliographic review carried out through searches of bibliographic references of relevant studies, in the online databases of Latin American and Caribbean Literature in Health Sciences (LILACS) and Scientific Electronic Library Online (SCIELO) and other sources. Inclusion criteria were articles available free of charge in Portuguese and English, prioritizing articles between 2015 and December 2022 that were related to the theme, and exclusion criteria were articles that were not similar to the object under study, studies carried out in animals or outside the established period. Results: Several intercurrences resulting from applications of hyaluronic acid and botulinum toxin on the face were observed in the literature. The complications observed are mild, but in some situations it can be serious; the most common are bruises, swelling, facial disfigurement. Conclusion: To minimize complications, professionals must use the correct techniques, products of origin, a good patient anamnesis, asepsis of the room and the equipment used. These intercurrences, when they occur, are harmful to patients, as they cause several negative factors such as depression, social seclusion, affect well-being and psychological imbalance.